A Study on Determination of an Optimized Detector for Single Photon Emission Computed Tomography - Khoshakhlagh, Mohammad (World J Nucl Med, 2016)
The detector is a critical component of the single photon emission computed tomography (SPECT) imaging system for giving accurate information from the exact pattern of radionuclide distribution in the target organ. The SIMIND Monte Carlo program was utilized for the simulation of a Siemen's dual head variable angle SPECT imaging system with a low energy high resolution (LEHR) collimator. The Planar and SPECT scans for a (99m)Tc point source and a Jaszczak Phantom with the both experiment and simulated systems were prepared and after verification and validation of the simulated system, the similar scans of the phantoms were compared (from the point of view of the images’ quality), namely, the simulated system with the detectors including bismuth germanate (BGO), yttrium aluminum garnet (YAG:Ce), Cerium-doped yttrium aluminum garnet (YAG:Ce), yttrium aluminum perovslite (YAP:Ce), lutetium aluminum garnet (LuAG:Ce), cerium activated lanthanum bromide (LaBr3), cadmium zinc telluride (CZT), and sodium iodide activated with thallium [NaI(Tl)]. The parameters of full width at half maximum (FWHM), energy and special resolution, sensitivity, and also the comparison of images’ quality by the structural similarity (SSIM) algorithm with the Zhou Wang and Rouse/Hemami methods were analyzed. FWHMs for the crystals were calculated at 13.895, 14.321, 14.310, 14.322, 14.184, and 14.312 keV and the related energy resolutions obtained 9.854, 10.229, 10.221, 10.230, 10.131, and 10.223 %, respectively. Finally, SSIM indexes for comparison of the phantom images were calculated at 0.22172, 0.16326, 0.18135, 0.17301, 0.18412, and 0.20433 as compared to NaI(Tl). The results showed that BGO and LuAG: Ce crystals have high sensitivity and resolution, and better image quality as compared to other scintillation crystals.